(3GdJUhjQ GdbQBfj ddbje GdNdbjI hGdJTQjYjI (B:s (3GdChGeQ hGdfhGgj (B/s - (3UHM, Ydj Ydj eUWai,s 1937- ((3GdbGgQI (B:s (3GdecJHI GdCRgQjI ddJQGK,s, 2020)
(3jJfGhd cJGH (B((3GdJUhjQ GdbQBfj ddbje GdNdbjI hGdJTQjYjI(B) (3hGdPj bGe HJCdjag (B((3Ydj Ydj UHM(B) (3aj MhGdj (B(2) (3eLdO ef GdbWY GdeJhSW, eSJYQVG GdeMJhjGJ GdJGdjI (B: (3ebOeI(B. (3Ke GdaUd GdChd (B: (3eYGde GdJUhjQ GdbQBfj, GdaUd GdKGfj (B: (3GdJUhjQ GdbQBfj dJYGbH Gddjd hGdfgGQ, GdaUd GdKGdK (B: (3GdJUhjQ GdbQBfj ddUhe hGdUjGe, GdaUd GdQGHY (B: (3JQHjI GdfTA heQGMdg aj GdJUhjQ GdbQBfj hGdSfI GdTQjaI, GdaUd GdNGeS (B: (3GdYbhO hGdeYGedGJ aj GdJUhjQ GdbQBfj hGdSfI GdTQjaI, hCNjQG (B: (3GdagGQS(B. s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3jJhGaQ HGdecJHI (B: (3eLdO (B1(3, (B2.s
Keywords: (3GdbQBf(B.s -- (3HdGZIs; (3GdbQBfs -- (3HdGZIs